Asianization, Multicultural tensions and Identity in John Romeril’s Miss Tanaka (2001) - Hassan Falah Hassan Al-Bayati; Asst. Prof. Thamir R. S. Az-Zubaidy (Journal of College of Education, 2026)
This paper examines the issue of Australian “Asianization”, which was adopted by Keating government (1991-1996), as one of the policies to consider the country’s geographical position in the continent. In so doing, the paper explores John Romeril’s Miss Tanaka (2001) to investigate how it reflects the nation’s “coming to terms” with its position in the Asia-Pacific region (Varney, 2009, p. 37). Further, it addresses the issue of cultural diversity through its cross-racial cast of characters. This layered theatrical approach situates Miss Tanaka as a key text in Australia’s broader cultural shift toward Asia, foregrounding the importance of multicultural narratives and identities within a regional framework. Further, relying on the works of scholars, such as Ien Ang, Gareth Griffiths, Graham Huggan, this paper explores the intricacies of identity and cultural amalgamation and reflect the extent to which Australian identity has been diverse. Further, the paper conveys how Romeril, in this play, celebrates Australia’s cultural diversity. It also demonstrates how the play challenges the claim that Australia’s identity is monolithic and critiques the white male gaze which considers the Asian female as a site of sexual desire.
Keywords: Asianization, male gaze, multiculturalism, Miss Tanaka, Romeril.